PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAM ACHIEVEMENT DIVISIONS) BERBANTU MEDIA POP UP BOOK TERHADAP HASIL BELAJAR IPS KELAS V SD NEGERI 6 MUARA RUPIT - Rika Novita Sari; Novianti Mandasari; Armi Yuneti (Genta Mulia : Jurnal Ilmiah Pendidikan, 2022)
AbstractThis study aims to determine the completion of social studies learning outcomes for fifth grade students of SD Negeri 6 Muara Rupit. The research method used is in the form of pre-experimental design with experimental design used in the form of one-group pre-test and post-test. In this study, one sample class was used, namely class V with 19 students. This means that all members of the population are sampled technique. The instrument used by the researcher was in the form of essay questions which collected 14 questions. Data collection was taken by using tests. The data were analyzed using the z-test formula. Based on the results of the data analysis test with a confidence level it ztounct = ztable 1,64. Because > thus, it can be concleded that the social studies learning outcomes of fifth grade students os SD Negeri 6 Muara Rupit after application of the STAD (Student Team Achievement Divisions) type cooperative learning model assisted by pop up book media on the social studies learning outcomes of class V SD Negeri 6 Muara Rupit significanty have been completed. keywords : STAD (Student Team Achievement Divisions), pop up book, IPS study result